Not just punishment: the overlooked harms of the criminal legal system - Fried, A (2023)
This thesis contains six essays that explore the ways in which people who are accused of or convicted of crimes are not just punished. Rather, people are mistreated and systematically harmed far before a trial conviction and far beyond a standard prison sentence. Each essay critically evaluates an overlooked problem in the practices of criminal legal systems. Chapter 1 presents a novel challenge for the justification of arrests. Chapter 2 argues that the practice of crediting time served demonstrates that pre-trial detention is actually pre-trial punishment. Chapter 3 brings together the literatures on testimonial injustice and criminal confessions to investigate the epistemic harms that occur at and around trial. Chapter 4 demonstrates that defense-introduced statistical evidence is not subject to the standard reasons provided to exclude statistical evidence from trial. Chapter 5 argues that unique features of the death penalty, unlike standard incarceration, render capital punishment inherently disproportional. Finally, Chapter 6 demonstrates how uncontroversial premises lead us to the surprising conclusion that there is a stronger argument in favor of compensation for guilty people who are over-punished than for innocent people who are incorrectly punished.